2021
DOI: 10.1155/2021/7925608
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Confining Pressure Unloading Rate on the Strength Characteristics and Fracture Process of Granite Using Lab Tests

Abstract: In order to study the mechanical behaviors and fracture process properties of granite under confining pressure unloading with constant axial pressure, RMT-150B rock mechanics test system and acoustic emission detector were used to study the mechanical properties and fracture process characteristics of deeply buried granite specimens under different combinations of initial confining pressures and unloading rates. The results show that when the unloading rate is small, the deviatoric stress-strain curve of grani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 28 publications
(24 reference statements)
0
1
0
Order By: Relevance
“…During the unloading process, the rock was dominated by lateral expansion deformation and brittle failure, resulting in the strong expansion becoming the root cause of the sudden and severe deformation and failure [12,13]. A low unloading rate is beneficial to the degree of rock fragmentation, while a high unloading rate contributes to the brittleness of the rock mass and damage [14][15][16]. Guo, Ji, and Cao [17] also indicated that a high unloading rate may increase the rock burst possibility.…”
Section: Introductionmentioning
confidence: 99%
“…During the unloading process, the rock was dominated by lateral expansion deformation and brittle failure, resulting in the strong expansion becoming the root cause of the sudden and severe deformation and failure [12,13]. A low unloading rate is beneficial to the degree of rock fragmentation, while a high unloading rate contributes to the brittleness of the rock mass and damage [14][15][16]. Guo, Ji, and Cao [17] also indicated that a high unloading rate may increase the rock burst possibility.…”
Section: Introductionmentioning
confidence: 99%